Identification of Students' Mastery Level of Physics Concepts in Static Fluid Material - Fatmawati , Fatmawati; Parno, Parno; Diantoro, Markus (Department of Physics Education, Universitas Mataram, 2025)
This study aims to identify the level of mastery of physics concepts on static fluid material. This research uses quantitative descriptive methods. The research subjects consisted of 23 MA students in Malang. The test instrument used was a four-point description question. The data collection process was carried out by distributing questions to students who were done for 60 minutes. The results showed that students' mastery of the concept of static fluid was in a very low category. The ability to remember (C1) students scored 51.1%, while the ability to understand (C2) reached 42.4%. The ability to apply (C3) was only 31.5%, and the ability to analyse (C4) reached 32.6%. The low mastery of this concept has an impact on the completion of tasks related to static fluid. Students experience various difficulties, such as assuming that the difference in hydrostatic pressure in a container depends on the shape of the container. Students also have difficulty in solving problems mathematically and assume that the longer the rope of the hanging object, the greater the buoyant force will be. Thus, the difference in buoyant force on an object suspended from a rope is considered to depend on the length of the rope. These findings emphasize the need to improve physics learning in the future, especially in improving the strengthening of the ability to master the concept of static fluid material.